1987
DOI: 10.1161/01.res.61.6.889
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on blood pressure and membrane-dependent vascular responses in the rat.

Abstract: Alterations in endothelium-dependent, sodium pump-mediated, and calcium-dependent responses of vascular smooth muscle were investigated in 5-7-, 24-26-, and 50-52-week-old male Sprague-Dawley rats. Age-dependent changes in systolic blood pressure were also determined. Although systolic blood pressure increased significantly with age, rats in all 3 age groups were considered normotensive. Initial studies on the passive force-response characteristics of strips of aortic and femoral arterial smooth muscle reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
3

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 36 publications
(25 reference statements)
2
33
0
3
Order By: Relevance
“…13,14 Endothelial dysfunction may result in an increase in the tone of small arteries that would reduce oscillatory compliance. 15 Experimental data indicate that aging alters endotheliumdependent relaxation in arteries, 16 and loss of the oscillatory waveform represents an early and consistent finding with aging and hypertension. 4,17 Different frequency fractions of the envelope waveform of the blood flow velocity possess different input resistances, meaning that individual oscillations of the harmonic content are exposed to different wave resistances, which are induced by both the peripheral reflexions and the vessel elasticity.…”
Section: Michelson Et Al Fourier Analysis Of the Flow Velocity Envelopementioning
confidence: 87%
“…13,14 Endothelial dysfunction may result in an increase in the tone of small arteries that would reduce oscillatory compliance. 15 Experimental data indicate that aging alters endotheliumdependent relaxation in arteries, 16 and loss of the oscillatory waveform represents an early and consistent finding with aging and hypertension. 4,17 Different frequency fractions of the envelope waveform of the blood flow velocity possess different input resistances, meaning that individual oscillations of the harmonic content are exposed to different wave resistances, which are induced by both the peripheral reflexions and the vessel elasticity.…”
Section: Michelson Et Al Fourier Analysis Of the Flow Velocity Envelopementioning
confidence: 87%
“…226 Also, coronary arteries from patients who had undergone heart transplantation, which are prone to atherosclerosis, either failed to dilate or paradoxically constricted to ACh. 248 Reduced endothelium-dependent relaxations were again seen in isolated aortas from old rats 249 and in pig coronary arteries made spastic by denudation of the endothelium 3 months previously. 250 Even slight damage to the endothelium can affect the formation of EDRF, for pial arterioles of anesthetized cats injured by a combination of mercury light and fluorescein dye lost their relaxant responses to ACh and bradykinin.…”
Section: Actions Of Edrfmentioning
confidence: 96%
“…In animals, chronic and acute elevation of blood pressure disturbs endothelium-dependent vasodilation.45 Age may also be a factor because older rats have an impaired acetylcholine dilator response when compared with younger animals. 21 Hodgson, using methylene blue (an inhibitor of the action of EDRF) suggested that acetylcholine is capable of releasing EDRF in humans. 22 In clinical studies, intracoronary acetylcholine infusion constricts coronary arteries when there is angiographic evidence of atherosclerosis in the studied vessel.10-12 However, controversy exists regarding the response of "normal" coronary arteries.101113 Furchgott1 described the endothelium-dependent vasomotor response of arteries to acetylcholine in vitro throughout a specific dose range.…”
Section: Diameter Responsesmentioning
confidence: 99%